The appropriation of hegemonic masculinity within selected research on men's health. Issue 1 (2nd January 2016) - Matthews, Christopher R.
Abstract : Connell's hegemonic masculinity thesis (HMT) has occupied a relatively dominant position within contemporary research exploring the lives of men. Messerschmidt has conducted a review of recent literature that purports to use HMT, he describes in detail some of the ways Connell's work has been appropriated. Taking Messerschmidt's lead, this paper explores a small selection of men's health research that employ HMT as a central organising theme. Such a narrow focus and limited sample enables the theoretical, conceptual and empirical contributions of engagements with Connell's work to be critically explored in detail. This paper provides colleagues with clear examples of ways in which reified and reductive account of masculinity, are still being reproduced in contemporary analyses of men's lives. In calling for researchers to critically reflect upon their usage of Connell's thesis in more detail, my aim is to increase the subtlety and sophistication of such works. A further hope is that by highlighting specific examples of the need to appraise the relevance and adequacy of HMT as a conceptual frame of lived experiences, we might encourage researchers to access the multitude of different theoretical positions that speak to the lives of men.